Crystal structure, morphology and sorption behaviour of porous indium-tetracarboxylate framework materials. Issue 44 (20th October 2015) - Qian, Jinjie; Yu, Panpan; Su, Kongzhao; Dong, Youqing; Huang, Shaoming; Hong, Maochun
Abstract : Structural and morphological transformations of two new indium-tetracarboxylate framework isomers from the same starting tetracarboxylate ligand are represented. Abstract : In this report, two totally new indium-tetracarboxylate framework isomers based on the same starting tetracarboxylate ligand are presented, namely, [Me2 NH2 ][In(BPTC)]·Guest (InOF-12 ) and [Hdabco][In(BPTC)]·Guest (InOF-13 ). Their corresponding crystal structures essentially originated from the guest templates and were then fully characterized and solved by single crystal X-ray diffraction analysis. Through low pressure gas capacity comparison, it is noted that desolvatedInOF-12 exhibits a better performance and its H2 isotherm reaches a high uptake capacity value of 1.32 wt% at 77 K and 1.0 bar, and a high carbon dioxide uptake of 82.2 cm 3 g −1 (3.67 mmol g −1 ) at 273 K and 1.0 bar, whileInOF-13 has a lower value of 80.4 cm 3 g −1 (3.59 mmol g −1 ) under the same conditions.